Refractory strictures despite steroid injection after esophageal endoscopic resection - Hanaoka, Noboru; Ishihara, Ryu; Uedo, Noriya; Takeuchi, Yoji; Higashino, Koji; Akasaka, Tomofumi; Kanesaka, Takashi; Matsuura, Noriko; Yamasaki, Yasushi; Hamada, Kenta; Iishi, Hiroyasu (Endoscopy International Open, 2016)
Background: Although steroid injection prevents stricture after esophageal endoscopic submucosal dissection (ESD), some patients require repeated sessions of endoscopic balloon dilation (EBD). We investigated the risk for refractory stricture despite the administration of steroid injections to prevent stricture in patients undergoing esophageal ESD. Refractory stricture was defined as the requirement for more than three sessions of EBD to resolve the stricture. In addition, the safety of steroid injections was assessed based on the rate of complications. Patients and methods: We analyzed data from 127 consecutive patients who underwent esophageal ESD and had mucosal defects with a circumferential extent greater than three-quarters of the esophagus. To prevent stricture, steroid injection was performed. EBD was performed whenever a patient had symptoms of dysphagia.Results: The percentage of patients with a tumor circumferential extent greater than 75 % was significantly higher in those with refractory stricture than in those without stricture (P = 0.001). Multivariate analysis adjusted for age, sex, history of radiation therapy, tumor location, and tumor diameter showed that a tumor circumferential extent greater than 75 % was an independent risk factor for refractory stricture (adjusted odds ratio [OR] 5.49 [95 %CI 1.91 – 15.84], P = 0.002). Major adverse events occurred in 3 patients (2.4 %): perforation during EBD in 2 patients and delayed perforation after EBD in 1 patient. The patient with delayed perforation underwent esophagectomy because of mediastinitis. Conclusions: A tumor circumferential extent greater than 75 % is an independent risk factor for refractory stricture despite steroid injections. The development of more extensive interventions is warranted to prevent refractory stricture.